Enucleations, Eviscerations, and Exenterations at a Supratertiary-care Hospital in Puerto Rico: A Retrospective Study - Rebollo, Nicole P.; Jiménez, Hiram J.; Ramírez, Ambar; Ortiz, Jan C.; Rodríguez, Julio A. (Puerto Rico Health Sciences Journal, 2022)
Objective: To provide a descriptive analysis of the indications and the intraoperative and postoperative complications of eye enucleations and eviscerations, and orbital exenterations performed at the only academic institution in Puerto Rico providing supratertiary care. Methods: A retrospective medical record review of patients who underwent enucleations, eviscerations, and exenterations from January 2015 through June 2020 was conducted. The data were analyzed to generate a descriptive profile of the demographic characteristics of the patients, their clinical indications and surgical complications, and a histopathological diagnosis per type of eye-removal procedure. Results: A total of 118 eyes were removed via enucleation, evisceration, or exenteration over the 66-month study period. The average patient age was 64 (±17.5) years and 63.8% of the patients were male. The most frequently performed eye-removal procedure was enucleation (73.7%), followed by evisceration (18.6%) and exenteration (7.6%). The main clinical indications for enucleations and eviscerations were infectious processes, namely panophthalmitis, endophthalmitis, and/or perforated corneal ulcers, that failed medical management. In our sample, squamous cell carcinoma was the most common diagnosis (both clinically and histopathologically) leading to exenteration. Postoperative complications in our patient cohort were minimal. Conclusion: At our institution, enucleations predominate over eviscerations. Retrospective reviews published in recent years indicate that the rate of eviscerations at our institution is comparatively low. The results of this study, the first of its kind at our institution, may encourage a re-evaluation of the indications for evisceration versus enucleation in our patient population.